BDNF Induces Calcium Elevations Associated With I(BDNF), a Nonselective Cationic Current Mediated by TRPC Channels - Amaral, Michelle D. (2007)
Brain-derived neurotrophic factor (BDNF) has potent actions on hippocampal neurons, but the mechanisms that initiate its effects are poorly understood. We report here that localized BDNF application to apical dendrites of CA1 pyramidal neurons evoked transient elevations in intracellular Ca(2+) concentration, which are independent of membrane depolarization and activation of N-methyl-d-aspartate receptors (NMDAR). These Ca(2+) signals were always associated with I(BDNF), a slow and sustained nonselective cationic current mediated by transient receptor potential canonical (TRPC3) channels. BDNF-induced Ca(2+) elevations required functional Trk and inositol-tris-phosphate (IP(3)) receptors, full intracellular Ca(2+) stores as well as extracellular Ca(2+), suggesting the involvement of TRPC channels. Indeed, the TRPC channel inhibitor SKF-96365 prevented BDNF-induced Ca(2+) elevations and the associated I(BDNF). Thus TRPC channels emerge as novel mediators of BDNF-induced intracellular Ca(2+) elevations associated with sustained cationic membrane currents in hippocampal pyramidal neurons.